Penerapan E-Tilang Dalam Penindakan Pelanggaran Lalu Lintas Guna Meningkatkan Pelayanan Publik Oleh Satuan Lalu Lintas Polresta Bogor Kota - Aryo, Maulana Hasyim (Indonesian Journal of Police Studies, 2020)
As technology develops and follows up on the program of the 22nd National Police Chief (2016-2019) Retired General Tito Karnavian namely PROMOTER on Improving public services that is easier for the public and based on information technology, the Korlantas Polri launches an E-ticket application as an innovation used as a substitute for conventional speeding tickets. Not long after the launching of the E-Tilang application by the National Police Traffic Police, the Bogor City Traffic Police Traffic Unit began implementing E-Ticket in carrying out traffic violations, but there were still some obstacles in its implementation. Based on this, this study intends to analyze the application of E-Traffic in the action of traffic violations in order to improve public services by the Bogor City Police Traffic Unit. The theory used in this thesis is Law Enforcement Theory, Management Theory. While the concept used is the E-ticketing Concept, the Concept of Traffic Violation Enforcement and the Concept of Public Servants. Furthermore, the Research Method through a qualitative approach and data obtained through interviews and observations and study documents analyzed by data reduction, data presentation and drawing conclusions. The results of research and discussion show that the application of E-ticketing by the Bogor City Police Traffic Unit has not been fully in accordance with the Concept in the enforcement of traffic violations and furthermore the application of E-ticketing in improving public services by the Bogor City Police Traffic Unit is not fully in accordance with the principles of public service that contained in Law No. 25 of 2009 concerning Public Services.